PEMAHAMAN AUDITOR TENTANG SKEMA KECURANGAN, RED FLAGS, MEKANISME DETEKSI DAN MEKANISME PREVENTIF KECURANGAN - Harti Budi Yanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
This study aims to determine the auditor’s understanding of the fraud scheme,indication of fraud, mechanism detection of fraud prevention mechanisms. This study uses primary data obtained through questionnaires. Totaled of 275 respondents from BPK auditors, internal auditors and external auditors in Jakarta. Fraud schemes are classified into three groups, cheating scheme of corruption, misappropriation of assets and fraudulent financial statements.Research results revealed that the majority of the auditors have to understand the fraud scheme with a good criteria, in the scheme of corruption, misappropriation of assets and fraudulent financial statements.